An Inheritance Saga: Migration, Kinship, and Postcolonial Bureaucracy in the Llorente vs. Llorente Case of Nabua, Philippines - Dada Docot (Humans, 2025)
The landmark Philippine Supreme Court case Llorente vs. Llorente illuminates the complex intersections of transnational migration, inheritance law, and colonial legacies in the Philippines. The case centers on Lorenzo Llorente, a Filipino US Navy serviceman whose estate became the subject of a fifteen-year legal battle between his first wife Paula and his second wife Alicia. Lorenzo returned from the battles of World War II to find his wife in Nabua living with his brother and pregnant with his brother’s child. Lorenzo obtained a divorce in California in 1952. He later returned to the Philippines and married Alicia, naming her and their three adopted children as heirs in his will. Upon his death in 1985, Paula challenged the validity of the US divorce and claimed rights to Lorenzo’s estate under Philippine succession laws. While lower courts initially favored Paula’s claims by rigidly applying Philippine laws that are rooted in the colonial era and privileged blood relations, the Supreme Court ultimately upheld Lorenzo’s will in 2000, recognizing his right to divorce as a US citizen. This case reveals how postcolonial Philippine legal frameworks, still heavily influenced by Spanish colonial law, often fail to accommodate the complex realities of transnational families and diverse kinship practices, instead imposing rigid interpretations that fracture rather than heal family relations. Inheritance, previously a highly shared and negotiated process mediated by the elders, can now escalate to family disputes which play out in the impersonal space of the courtroom.